Bone remodeling using a three-dimensional chitosan - hydroxyapatite scaffold seeded with hypoxic conditioned human amnion mesenchymal stem cells - Michael Josef Kridanto Kamadjaja (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Bone regeneration studies involving the use of chitosan–hydroxyapatite (Ch-HA) scaffold seeded with human amnion mesenchymal stem cells (hAMSCs) have largely incorporated tissue engineering experiments. However, at the time of writing, the results of such investigations remain unclear. Purpose: The aim of this study was to determine the osteogenic differentiation of the scaffold Ch-HA that is seeded with hAMSCs in the regeneration of calvaria bone defect. Methods: Ch-HA scaffold of 5 mm diameter and 2 mm height was created by lyophilisation and desalination method. hAMSCs were cultured in hypoxia environment (5% oxygen, 10% carbon dioxide, 15% nitrogen) and seeded on the scaffold. Twenty male Wistar rat subjects (8 – 10 weeks, 200 - 250 grams) were randomly divided into two groups: control and hydroxyapatite scaffold (HAS). Defects (similar size to scaffold size) were created in the calvaria bone of the all-group subjects, but a scaffold was subsequently implanted only in the treatment group members. Control group left without treatment. After observation lasting 1 and 8 weeks, the subjects were examined histologically and immunohistochemically. Statistical analysis was done using ANOVA test. Results: Angiogenesis; expression of vascular endothelial growth factor; bone morphogenetic protein; RunX-2; alkaline phosphatase; type-1 collagen; osteocalcin and the area of new trabecular bone were all significantly greater in the HAS group compared to the control group. Conclusion: The three-dimensional Ch-HA scaffold seeded with hypoxic hAMSCs induced bone remodeling in calvaria defect according to the expression of the osteogenic and angiogenic marker.